1988
DOI: 10.1126/science.2449732
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Precursors Can Give Rise to All Major Cell Types of the Frog Retina

Abstract: A prospective lineage analysis was performed to determine the variety of cell types that could be formed by individual precursor cells of the developing frog retina. Fluorescent dextran was iontophoretically injected into single cells of the embryonic optic vesicle. After further development of the embryo, labeled descendants were observed in all three layers of the larval retina. Furthermore, different clones were composed of various combinations of all major cell types, including the glial Müller cells. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
314
2
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(325 citation statements)
references
References 19 publications
8
314
2
1
Order By: Relevance
“…Lineage tracing and birth dating experiments demonstrated that all of the neuronal cell types in the retina are derived from a common multi-potent progenitor cell (Turner and Cepko, 1987;Wetts and Fraser, 1988). For photoreceptor cells, cones are usually born (exit from the mitotic cycle and commit to the photoreceptor lineage) earlier than rods.…”
Section: Introductionmentioning
confidence: 99%
“…Lineage tracing and birth dating experiments demonstrated that all of the neuronal cell types in the retina are derived from a common multi-potent progenitor cell (Turner and Cepko, 1987;Wetts and Fraser, 1988). For photoreceptor cells, cones are usually born (exit from the mitotic cycle and commit to the photoreceptor lineage) earlier than rods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have examined cell lineage in the vertebrate central nervous system (CNS) to see whether neuronal and glial cell types originate from a common precursor or from distinct progenitors (Kornack and Rakic 1995;Reid et al 1995;for review, see Luskin 1994). In cortex (Price and Thurlow 1988;Walsh and Cepko 1988), retina ITurner and Cepko 1987;Holt et al 1988;Wetts and Fraser 1988), and optic tectum (Galileo et al 1990), a single precursor cell can give rise to both neurons and glia as well as different types of neurons even at late stages of neurogenesis. These results imply that multipotential precursors persisting throughout CNS development differentiate in response to local cues.…”
Section: [Abstract: Stem Cells; Neurons; Glia]mentioning
confidence: 99%
“…A third possibility is that the addition of SHH-N promotes the proliferation of progenitors at an advanced stage of rod photoreceptor commitment. Although vertebrate retinal progenitors are multipotent (Turner and Cepko, 1987;Holt et al, 1988;Wetts and Fraser, 1988), studies have shown heterogeniety in the responses of retinal progenitors to growth factors and cyclic nucleotide analogs (Taylor and Reh, 1990;Lillien and Cepko, 1992). Furthermore, expression of basic helixloop-helix transcription factors such as Mash I and Cash I are differentially expressed in retinal progenitors at mid to late stages of retinal development in the mouse and chick, respectively (Jasoni et al, 1994;Jasoni and Reh, 1996).…”
Section: Hedgehog Proteins Promote Photoreceptor Differentiation In Vmentioning
confidence: 99%